Research of Measuring Device in Surface of Road Temperature - Won Bang, Gul; Ho Kim, Yong (International Journal of Engineering and Technology, 2018)
Background/Objectives: Measuring device of road surface temperature installed all kinds of road makes it possible to predict not only road surface temperature as well as its trend of temperature change by providing real time information of road surface temperature which has an important effect of ice on the road in winter season but also time invested in snow removal and workload. It is suggested method to improve measurement precision of road surface temperature.Methods/Statistical analysis: Sample is installed in a constant temperature chamber before test implementation and leaves it in natural conditions without configuring settings to make upper surface temperature becoming constant temperature. Upper surface temperature leaves until a certain temperature after setting below zero temperature when the target temperature is reached.Findings: Correction formula that is satisfied maximum error rangeÂ±0.5â„ƒ between surface temperature of concrete test piece and temperature correction through measuring device is drawn based on analysis of trend in measuring device of the temperature change and its gradient.Improvements/Applications: Surface temperature measuring device applied correction formula increases the accuracy of surface road temperature as an important factor of ice protection system on the road and the effect of preventing traffic accident due to freezing will be increased.